How Intraday Index Changes Influence Periodontal Assessment: A Preliminary Study - Carlo Bertoldi; Andrea Forabosco; Michele Lalla; Luigi Generali; Davide Zaffe; Pierpaolo Cortellini (International Journal of Dentistry)
It is reputed that periodontal indices remain unchanged over a 24-hour period, with great clinical significance. This preliminary study analyzes daily index changes. In 56 selected patients, full-mouth plaque score (FMPS), full-mouth bleeding score (FMBS), periodontal screening and recording (PSR) indices, and periodontal risk assessment (PRA) were recorded at baseline and three times per day (check-I: 08.30, check-II: 11.30, and check-III: 14.30), after appropriate cause-related therapy. Correlation between variables was statistically analyzed by Stata. All periodontal indices improved at the examination phase. Statistical differences were detected for FMPS comparing all thrice daily checks. Statistical differences were detected for FMBS and PRA comparing check-III with check-I and check-II. PSR showed no significant changes. The worst baseline indices produced the widest daily fluctuation at the examination phase. Significant variation of indices is directly related to clinical severity of periodontal conditions at baseline. Patients affected by severe periodontal disease may show significantly greater index changes. As indices are routinely recorded only once per day, the index daily variation has clinical significance. This greatly affects therapeutic strategy as correct periodontal assessment requires multiple evaluations at standardized times, particularly when baseline conditions are severe.